Pentingnya Etika Akademik dalam Konteks Tradisi Islam - Eyzi Pratiwi; Ira Suryani; Iga Nailah Aulia; Khairunnisa Khairunnisa; Putri Amanda Fadilla; Tri Fauziah Hasanah (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Academic ethics in the Islamic tradition emphasizes honesty, integrity and responsibility. This paper aims to explain the impact of the principles of academic ethics in the Islamic tradition on the education and development of Islamic society. The Islamic tradition has strong ethical principles, including in an academic context. The principles of academic ethics in the Islamic tradition emphasize honesty, integrity and responsibility. The principles of academic ethics in the Islamic tradition can help improve the quality of education and the development of Islamic society. In an educational context, these principles help foster discipline, honesty and hard work in students. Students who follow the principles of academic ethics in the Islamic tradition will be able to develop their academic potential more effectively. In the context of community development, the principles of academic ethics in the Islamic tradition help create a society that is cultured, moral and has high integrity. Communities that have strong ethical principles will be better able to build healthy and harmonious relationships between individuals and groups.